Natriuretic peptides as novel regulators of dendritic cells-mediated inflammation - Giorgia Manni; Estevao Carlos Silva Barcelos; Doriana Ricciuti; Benedetta Pieroni; Marco Gargaro; Giulia Mencarelli; Hans Acha-Orbea; Vincenzo Nicola Talesa; Letizia Mezzasoma; Francesca Fallarino (Cellular and Molecular Life Sciences)
Abstract Natriuretic Peptides (NPs), including atrial (ANP) and brain (BNP) types, exert pleiotropic effects in regulating immune responses via the Natriuretic Peptide Receptor-1 (NPR1), expressed across various immune cells. While NPs are established inhibitors of inflammasome activation and IL-1β secretion in human monocytes, their role in dendritic cells (DCs)-key regulators of innate and adaptive immunity-remains unclear. Inflammasome activation in DCs can yield both protective and detrimental outcomes depending on the context of the disease, suggesting that modulating this pathway could offer a promising pharmacological strategy for controlling immune responses. This study explored the regulation of the NLRP3 inflammasome by NPs in two conventional DC subsets: cDC1 and cDC2. We found that both subsets express basal levels of the NPR1 receptor, which increase under inflammatory conditions. Additionally, cDCs themselves produce ANP and BNP during inflammation. Although both subsets express basal levels of NLRP3 inflammasome proteins, cDC2 display a more robust NLRP3/IL-1β activation in response to LPS + ATP stimulation compared to cDC1. Notably, the NPs/NPR1 axis suppresses NLRP3 activation more effectively in the cDC2 subset by acting at translational and post-translational levels. These findings highlight NPs as a novel mechanism for controlling the inflammatory phenotype of cDCs and underscores NPs/NPR1 axis as therapeutic target for immune modulation of DC subsets. Graphical abstract cDC1 and cDC2 are equipped with the ANP/BNP–NPR1 axis and are sensitive to NLRP3 inflammasome activation. The natriuretic peptides ANP and BNP, through NPR1, represent a novel immunoregulatory mechanism that more effectively suppresses the inflammatory response in cDC2s than in cDC1. The NPs/NPR1 axis emerges as a potential therapeutic target for the control of pathological inflammation. Created in BioRender. https://BioRender.com/nrcr3m9